PENGARUH PROFITABILITAS, BESARAN PERUSAHAAN, LEVERAGE, DAN PERTUMBUHAN PERUSAHAAN TERHADAP KEBIJAKAN DIVIDEN - Tigris Hans Goldwin; Sri Handayani (Diponegoro Journal of Accounting, 2022)
This study aims to examine the effect of Profitability, Firm Size, Leverage, and Growth on Dividend Policy. The dependent variable in this study is dividend policy which is measured using the Dividend Payout Ratio (DPR), the independent variables in this study are Profitability, Firm Size, Leverage, and Growth.This research was conducted using quantitative methods using data from financial industry companies in the banking sector listed on the Indonesia Stock Exchange in 2015-2019 . Sampling was done by purposive sampling method which finally got 20 of the 46 companies listed on the BEI page with a total sample of 100 companies from the population. The research data were analyzed using multiple regression analysis with SPSS software for hypothesis testing.The results showed that profitability and firm size had significant positive effect on dividend policy. Meanwhile leverage and growth have no significant effect on dividend policy.